PERENCANAAN GEDUNG MENARA BANK MEGA SEMARANG - Firdaus Bagus Alya; Ichsan Ramadhani; Nuroji Nuroji; Rudi Yuniarto Adi (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Planning for earthquake resistant buildings are earthquake-resistant buildings shaken though maybe some buildings damaged when a massive earthquake but may remain standing. In designing earthquake-resistant structures necessary to review the methods of nonlinear structural properties (ductility, R, verification earthquake loads Vb). According to SNI 03-2847-2002, planning buildings to areas with high seismic risk using System Framework bearer Special Event (SRPMK). Moment Frame Systems bearer is a space frame system in which the structural components and join-joinnya resist the forces that work through the action of bending, shear and axial where the calculation of the structure of the frame bearer Special Event System is designed to use the concept of Weak Beam Strong Colomn designed so that the building can respond to earthquakes by developing joint mechanism of plastic on his logs and beam-column basis.